Development of commercial flood depth-damage curve for Kuantan, Pahang - Shafieq Aiman, Shamsuddin (2019)
Floods caused great consequences to communities and individuals. As most people are well aware, the immediate impacts of flooding include loss of life, damage to property, destruction of crops, loss of livestock, and deterioration of health conditions owing to waterborne diseases. The consequences of flooding are normally assessed by flood vulnerability assessment. However, in Malaysia, the studies on flood vulnerability are limited especially on flood damage. Therefore, the main purpose of this study is to assess flood damage during the 2013 Kuantan flood. Interview survey was conducted to collect the damage information. The regression analysis was performed to determine the factors that effects the level of flood damage and a depth-damage curve was developed to show the relationship between the damage in percentage and flood depth. The percentage of damage was obtained by dividing the actual damage with estimated damage. The result shows that content damage is higher than structural damage. The average content damage for two level premises is RM42,971, compared to RM5,609 for structural damage. While content damage for single level premises is lower which is RM23,103 (content) and RM4,161 (structural). According to the type of business, good & services content damage is higher (RM35,974) compared to food and beverages (RM11,813). The structural damage for both business category is lower which is RM5,063 and RM5,609 respectively. Regression analysis shows that business income and type of business are the variables that effects the level of content damage, while the structural damage was influenced only by the level of building. The R² for flood depth-damage curve is good enough which are 0.91 and 0.86 for content and structural damage respectively and can be used for future studies on flood risk assessment at the study area.